Performance Analysis of IRS-Assisted Multi-Link FSO System Under Pointing Errors - Takumi Ishida; Chedlia Ben Naila; Hiraku Okada; Masaaki Katayama (IEEE Photonics Journal)
The integration of intelligent reflecting surfaces (IRS) into free-space optical (FSO) communication systems is considered as a promising and innovative approach to overcoming existing challenges due to the strict line-of-sight (LoS) requirements faced by conventional FSO setups, thereby ensuring more flexible and controllable links and expanding the communication coverage area. Nonetheless, the configuration of IRS-assisted FSO systems remains relatively novel, requiring investigation into optimizing IRS placement to enhance system performance while mitigating interference and obstacles in dynamic environmental conditions. This work aims to evaluate the improvement of the system performance achieved through optimized IRS positioning while accounting for the main degrading factors inherent in FSO systems and IRS design. We present a comprehensive model for a multilink terrestrial IRS-assisted FSO system, taking into consideration key degrading factors such as pointing errors stemming from both transmitter and IRS jitter, IRS dimensions, and turbulence-induced fading. Furthermore, we derive closed-form expressions for the probability density function of channel coefficients, average bit error rate, and outage probability. Our results indicate that optimal IRS placement is in proximity to the transmitter, taking into account all channel impairments. Furthermore, we showed that optimal IRS placement tends to shift towards the receiver side as the IRS jitter increases. Consequently, the analysis presented offers valuable insights for efficiently designing IRS-assisted FSO systems, particularly regarding IRS placement in the presence of pointing errors.